Optimalisasi Potensi Sumber Daya Lokal dan Infrastruktur Melalui Pemberdayaan Masyarakat Desa Oemofa - Stefanus Neno; Rya Tadeus (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2025)
This community service activity was carried out in Oemofa Village with the aim of optimizing the potential of local resources and infrastructure through community empowerment. The method employed was a participatory approach, which included field observation surveys, focus group discussions (FGDs), training programs, and monitoring and evaluation. The results of the community service were implemented according to the initially planned stages. The activities were conducted together with the people of Oemofa Village, faculty members, and students from the Albert Foenay Institute of Technology. The activities included the installation of trash bins at the Oemofa market, tree planting in the courtyard of the sub-district office, a community service event in Dusun Satu involving all residents, the creation of a signboard for the Posyandu (integrated health post) named Tunas Mekar, and the development of an information board which is highly needed at the sub-district office, along with several other supporting programs. These activities contributed to strengthening the independence and welfare of the village community.